MiR‐146a protects small intestine against ischemia/reperfusion injury by down‐regulating TLR4/TRAF6/NF‐κB pathway. Issue 3 (25th August 2017) - He, Xuemei; Zheng, Yingqiang; Liu, Shengzhi; Shi, Sen; Liu, Yong; He, Yanzheng; Zhang, Chunxiang; Zhou, Xiangyu
Abstract : Previous studies reported that miR‐146a was involved in small intestine ischemia‐reperfusion (I/R) injury, but the mechanism is largely vague. Here, we aimed to identify the change of miR‐146a in patients with mesenteric ischemia and explore the potential regulatory mechanism of miR‐146a in intestine epithelial cells survival under ischemia and I/R injury. The plasma of 20 patients with mesenteric ischemia and 25 controls was collected to examine the miR‐146a expression by qPCR. Rat intestinal epithelial cells (IEC‐6) and 24 male Sprague–Dawley rats were included to build ischemia and I/R model in vitro and in vivo. The qPCR results showed that miR‐146a decreased both in the plasma of patients with mesenteric ischemia and in IEC‐6 cells and rat small intestine tissues in ischemia and I/R model compared to controls. Both the in vitro and in vivo results showed that I/R resulted in more severe apoptotic injury than ischemia. Cleaved‐caspase 3, TLR4, TRAF6, and nuclear NF‐κB p65 were up‐regulated accompanying reduced XIAP and SOCS3 expression in intestinal ischemia and I/R injury. After up‐regulation of miR‐146a in IEC‐6 cells, increased cell survival and decreased cell apoptosis were observed, concomitant with decreased cleaved‐caspase 3 and down‐regulated TLR4/TRAF6/NF‐κB pathway. What is more, this protective effect was blocked by TRAF6 overexpression and increased nuclear NF‐κB p65 nuclear. Taken together, this study revealed that miR‐146a expression was decreased in small intestine ischemia and I/R injury. And miR‐146a improves intestine epithelial cells survival under ischemia and I/R injury through inhibition TLR4, TRAF6, and p‐IκBα, subsequently leading to decreased NF‐κB p65 nuclear translocation. Abstract : miR‐146a expression was decreased in small intestine ischemia and I/R injury. And miR‐146a improves intestine epithelial cells survival under ischemia and I/R injury through inhibition TLR4 and TRAF6, subsequently leading to decreased NF‐κB p65 nuclear translocation.